The Effect of the Lost Twin Game on Students' Pronunciation Performance - Rabi'ah Rabi'ah; Achmad Baidawi; Wahab Syakhirul Alim (IJEE (Indonesian Journal of English Education), 2020)
ABSTRACTThe objective of this study was to examine whether the use of the Lost Twin Game in teaching pronunciation affects students' pronunciation and how significant the effect is on their pronunciation performance. This research was motivated by the phenomenon that there are various obstacles to teaching pronunciation at the school level including those related to students’ personal characteristics and teachers’ instructional methods. The participants of this study were eighth grade students of MTs Nasrul Ulum Bagandan Pamekasan, consisting of 20 students. This research is pre-experimental utilizing a pretest and posttest, and the data for this study were analyzed statistically using a t-test with SPSS 20. The results of this study show that the t-value 0.000 is lower than 0.05 which means that there is a significant effect of the treatment on the students’ pronunciation performance, and the treatment also accounts for the students' score increase by about 25%. It is, thus, concluded that the incorporation of the Lost Twin Game in teaching pronunciation is effective in improving students' pronunciation performance. ABSTRAKTujuan dari penelitian ini adalah untuk menguji apakah penggunaan Lost Twin Game dalam pengajaran pelafalan mempengaruhi pelafalan siswa dan seberapa signifikan pengaruhnya terhadap kinerja pelafalan mereka. Penelitian ini dilatarbelakangi oleh fenomena adanya berbagai kendala dalam pembelajaran pengucapan di tingkat sekolah termasuk yang berkaitan dengan karakteristik pribadi siswa dan metode pembelajaran guru. Partisipan dalam penelitian ini adalah siswa kelas VIII MTs Nasrul Ulum Bagandan Pamekasan yang berjumlah 20 orang. Penelitian ini merupakan penelitian praeksperimental dengan menggunakan pretest dan posttest, dan data untuk penelitian ini dianalisis secara statistik menggunakan uji-t dengan SPSS 20. Hasil penelitian ini menunjukkan bahwa t-value 0,000 lebih kecil dari 0,05 yang berarti ada pengaruh yang signifikan dari perlakuan terhadap kinerja pengucapan siswa, dan perlakuan tersebut juga menyebabkan peningkatan nilai siswa sekitar 25%. Dengan demikian, disimpulkan bahwa penggunaan Lost Twin Game dalam pengajaran pengucapan efektif dalam meningkatkan kinerja pengucapan siswa. How to Cite: Rabi'ah, Baidawi, A., Alim,  W. S. (2020). The Effect of the Lost Twin Game on Students' Pronunciation Performance. IJEE (Indonesian Journal of English Education), 7(1), 63-71. doi:10.15408/ijee.v7i1.16995